The role of the cumulus oophorus complex during spermatozoa capacitational events - Rijsdijk, Michelle (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Obstetrics and Gynaecology))--University of Stellenbosch, 2005.